Ms. Marvel. 9, Teenage Wasteland - Wilson, G. Willow, 1982- (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2018)
Kamala Khan has all but disappeared from Jersey City's crime fighting scene, and in her wake a new hero and ordinary citizens have rushed to fill the void, but the return of an old enemy may be enough to force her hand.